Mechanisms by Which Chronic Ethanol Feeding Impairs the Migratory Capacity of Cutaneous Dendritic Cells. (29th July 2013) - Parlet, Corey P.; Schlueter, Annette J.
<x xml:space="preserve">Abstract</x> Background Chronic alcoholism is associated with increased incidence and severity of skin infection. Cutaneous dendritic cells (CDCs) play a pivotal role in skin immunity, and chronic ethanol (EtOH) feeding in mice has been shown to inhibit CDC migration to skin‐draining lymph nodes (dLNs) following epicutaneous sensitization. Because CDC subsets differentially initiate T‐cell responses, it is important to determine how EtOH feeding affects migration of each subset and identify mechanisms responsible for observed defects. Methods Mice received EtOH in the drinking water for ≥ 16 weeks. Baseline numbers of CDC subsets and their migration to the dLNs following fluorescein 5‐isothiocyanate (FITC) sensitization were assessed by flow cytometry. Epidermal cell suspension and skin explant cultures were used to measure the impact of EtOH upon molecules that influence CDC migration. Cytokine arrays performed on explant culture supernatants assessed local production of inflammatory cytokines. Results Chronic EtOH feeding reduced migration of all CDC subsets to the dLNs following FITC sensitization. Reduced migration of dermal‐resident CDCs did not correspond with reduced baseline numbers of these cells. For Langerhans cells (LCs), EtOH‐induced migratory dysfunction corresponded with delayed down‐regulation of E‐cadherin, chemokine receptor 1 (CCR1), and CCR6 and impaired up‐regulation of matrix metalloproteinases (MMPs) 2 and 9. In skin explant assays, EtOH blunted CDC mobilization following stimulation with CCL21/CPG 1826. No alteration in CD54 or CCR7 expression was observed, but production of skin‐derived tumor necrosis factor alpha (TNF‐α) was reduced. Poor migratory responses in vitro could be improved by supplementing explant cultures from EtOH‐fed mice with TNF‐α. Conclusions Chronic EtOH consumption does not alter baseline dermal‐resident CDC numbers. However, like LCs, migratory responsiveness of dermal CDCs was decreased following FITC sensitization. Inefficient down‐regulation of both CCRs and adhesion molecules and the inability to up‐regulate MMPs indicate that EtOH impedes LC acquisition of a promigratory phenotype. These defects, combined with improvement of the migratory defect with in vitro TNF‐α replacement, demonstrate intrinsic as well as environmental contributions to defective CDC migration. These findings provide novel mechanisms to explain the observed increased incidence and severity of skin infections in chronic alcoholics.